Model Predictive Control for UAV Automatic Landing on Moving Carrier Deck with Heave Motion. Issue 5 (2015) - Koo, Soyeon; Kim, Seungkeun; Suk, Jinyoung
Abstract: This paper investigates a model predictive automatic carrier landing system considering the motion of carrier. With the medium-altitude long-endurance UAV and carrier models, the guidance and control for safe shipboard landing use the relative geometry between the UAV and carrier deck into account. The automatic carrier landing system is operated by two types of control systems. One is the linear quadratic tracker with integral designed to track the desired glide slope. The other is the model predictive control which finds the optimizing control input sequences over a certain time horizon by predicting the future motions of the UAV and the carrier deck. Numerical simulations are performed for an UAV and a carrier with heave motion to verify the feasibility of the proposed approach.